Developing a parenting program for young couples - Nurul Hidayah; Fuadah Fakhruddiana; Ega Asnatasia Maharani (Intelektual Pustaka Media Utama, 2021)
In support of developing a parenting program for young couples, this study conducted to determine whether and how significantly the module was affects parenting practice among young couples in a small groups. Data were collected through experimental research. The subjects of this research were young couples with requirements as follows: have children whose age is maximum five years old, graduated from high schools, able to communicate fluently, and are willing to attend all interventions and are not joining any similar training. The subjects were 26 parents who are domiciled in the Province of the Special Region of Yogyakarta, Indonesia and recruited through social media. The data analysis technique was a paired sample t-test. The result indicated -6.299 value t and value p=0.000 or (p less than 0.01). It showed a significant development of parenting comprehension before and after training (mean pretest is about 62.13 and mean post-test is about 78.26). This parenting program module needs to be tested in the wider population to form into final results.